Analysis of visual mechanisms and their importance in sensorimotor coordination. - Cervantes Pérez, Francisco (Revista Mexicana de Ingenieria Biomedica, 1991)
In this paper we present the analysis of in-in and inside-out processes that are carried out by the interaction between several regions of the nervous system. Likewise, we realize the importance of carrying out multidisciplinary studies that involve the theory-experiment combination, to analyze possible mechanisms used by the central nervous system to control the animal's behavior under different specific situations.